2021
DOI: 10.1007/s11356-021-15898-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the nexus among sulfur dioxide emission, energy consumption, and economic growth: empirical evidence from Pakistan

Abstract: Developing countries like Pakistan majorly depends on fossil fuels for achieving higher economic growth but have sloppy environmental rules and regulations in order to attract foreign direct investment (FDI). As a result, energy consumption is considered as the primary cause of environmental degradation. Besides CO2 emission, environmental degradation is also associated with emission of sulfur dioxide (SO2). The purpose of this study was to investigate the relationship among SO2 emissions, energy consumption, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 74 publications
3
10
0
Order By: Relevance
“…This research ascertains the significant positive effect of capital in both the short and long run, proving that capital is the major driver of economic growth. These findings concur with past research postulations, which emphasized the importance of capital in encouraging the economic growth of a nation (Bakhsh et al , 2021). The theories of production, such as the Cobb–Douglas production function, which project capital as the major determinant of output, are also supported (Mankiw, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This research ascertains the significant positive effect of capital in both the short and long run, proving that capital is the major driver of economic growth. These findings concur with past research postulations, which emphasized the importance of capital in encouraging the economic growth of a nation (Bakhsh et al , 2021). The theories of production, such as the Cobb–Douglas production function, which project capital as the major determinant of output, are also supported (Mankiw, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…The positive effect of NRE on CO 2 emissions shows that NRE is the major driver of environmental degradation. The findings concur with those reported in past researches, which shows that NRE causes CO 2 emissions to increase (Boukhelkhal, 2021; Deka et al , 2022c; Bakhsh et al , 2021; Akadiri and Adebayo, 2021). The positive effect of tourism arrivals on CO 2 emissions in this study does not concur with past studies, which alluded that tourism arrivals negatively impact the quality of the environment (Danish and Wang, 2018; Robaina-Alves et al , 2016; Shaheen et al , 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Majeed and Ashiq (2019) also find the favorable role of FDI in the economic growth of Pakistan over the period 1976-2016. Bakhsh et al (2022) conclude the same results for a significant positive impact of FDI on economic growth in the case of Pakistan. Certainly, investment patterns over the globe have changed since the fourth industrial revolution.…”
Section: Kof Indexsupporting
confidence: 74%
“…Combining the results of Tables 4 and 6, we find that the industrial structure, human capital, opening to the outside world, and investment in science and education are the main ways that CRZ policies affect SO 2 emissions. In fact, Bakhsh and Akmal et al, also found that FDI and population density are significantly related to SO 2 emissions [90]. Contacting the specific implementation of the CRZ policy, we explain the impact mechanism as follows.…”
Section: Discussion Of the Mechanism Analysesmentioning
confidence: 93%